Adding hydrated lime for improving microstructure and mechanical properties of mortar for ultra-high performance concrete. (May 2023) - Zhang, Gui; Peng, Gai-Fei; Zuo, Xue-Yu; Niu, Xu-Jing; Ding, Hong
Abstract: Because of the insufficient calcium hydroxide content required for the pozzolanic reaction in ultra-high performance concrete (UHPC) incorporating high-volume mineral admixtures, hydrated lime was intentionally added to the mortar used for UHPC to investigate its influence on the compressive strength and splitting tensile strength of mortar. The mechanism of the effect of hydrated lime on the mechanical properties of mortar was analysed by microstructural tests, including X-ray diffraction (XRD), thermogravimetric analysis (TGA), environmental scanning electron microscopy ( E -SEM), and mercury intrusion porosimetry (MIP). The results showed that supplementary hydrated lime at various proportions was conducive to the improvement in the mechanical properties of mortar under the combined curing of hot water at 90 °C and subsequent dry-air heating at 250 °C. The improvement in mechanical properties was due to the transformation of calcium-(aluminium)-silicate-hydrate (C-(A)-S-H) gels generated by the pozzolanic reaction into crystalline tobermorite and xonotlite and the subsequent refinement of the microstructure. Furthermore, a denser microstructure and better mechanical properties were achieved when the pozzolanic reaction and cement hydration reached an optimal balance, accompanied by a relatively high content of crystallised phases, including tobermorite and xonotlite.